Poverty in the Philippines: Its Social Roots - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 4 No 4 (1989), 2008)
How is poverty in the Philippines reproduced or why has it persisted? The article tried to sketch a picture of everyday life in an economically depressed rural community. It will now attempt to complement this by quantifying the dimensions or marginal and subsistence living in the Philippines. It focuses attention on the social structures that reproduce poverty, and demonstrates the futility of current government efforts to improve the living conditions of those who are regarded as the bottom poor in the society.